The Genetic Landscape of Cutaneous Lupus Erythematosus - Chen, Henry W.; Barber, Grant; Chong, Benjamin F. (Frontiers in Medicine, 2022)
Cutaneous lupus erythematosus (CLE) is an autoimmune, connective tissue disease that can exist as its own disease entity or within the context of systemic lupus erythematosus (SLE). Over the years, efforts to elucidate genetic underpinnings of CLE and SLE have yielded a wealth of information. This review examines prior studies investigating the genetics of CLE at the DNA and RNA level and identifies future research areas. In this literature review, we examined the English language literature captured within the MEDLINE and Embase databases using pre-defined search terms. First, we surveyed studies investigating various DNA studies of CLE. We identified three predominant areas of focus in HLA profiling, complement deficiencies, and genetic polymorphisms. Elevated frequency of HLA-B8 has been strongly linked to CLE. Also, multiple genes responsible for mediating innate immune response, cell growth, apoptosis, and interferon response confer a higher risk of developing CLE, specifically TREX1 and SAMHD1. There was a strong association between C2 complement deficiency and CLE. Second, we reviewed literature studying aberrations in the transcriptomes of CLE patients. We reviewed genetic aberrations initiated by environmental insults, and we examined the interplay of dysregulated inflammatory, apoptotic, and fibrotic pathways in the context of the pathomechanism of CLE. These current learnings will serve as the foundation for further advances in integrating personalized medicine into the care of CLE patients.